2005
DOI: 10.1002/chem.200500616
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding and Dynamic Behaviour in Crystals and Polymorphs of Dicarboxylic–Diamine Adducts: A Comparison between NMR Parameters and X‐ray Diffraction Studies

Abstract: Fumaric, malonic, maleic, and hydromuconic (HOOCCH2(CH)2CH2COOH) acids were used to prepare a series of hydrogen-bonded adducts or salts, depending on whether acid-base proton transfer takes place, with the dibase [N(muCH2CH2)3N] in various stoichiometric ratios. The resulting compounds have been investigated by using the 1H MAS, 15N, and 13C cross polarisation magic-angle spinning (CPMAS) methods and discussed in relation to X-ray diffraction studies to ascertain the nature of the O-HO, NH-O, and N+-HO- hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 68 publications
3
62
0
Order By: Relevance
“…This is in agreement with the co‐crystal nature of the adducts observed by single‐crystal X‐ray diffraction and confirmed by 15 N CPMAS spectra. Several 15 N NMR studies on hydrogen‐bonded systems have shown that formation of hydrogen bonds results in high‐ or low‐frequency shifts of the nitrogen signal, according to the type of nitrogen atom and the nature of the interaction 13c. 15df In our case, the free bipyridine nitrogen signal falls at δ =288.2 ppm, whereas in the three co‐crystal forms it falls around δ =262 ppm.…”
Section: Resultsmentioning
confidence: 54%
“…This is in agreement with the co‐crystal nature of the adducts observed by single‐crystal X‐ray diffraction and confirmed by 15 N CPMAS spectra. Several 15 N NMR studies on hydrogen‐bonded systems have shown that formation of hydrogen bonds results in high‐ or low‐frequency shifts of the nitrogen signal, according to the type of nitrogen atom and the nature of the interaction 13c. 15df In our case, the free bipyridine nitrogen signal falls at δ =288.2 ppm, whereas in the three co‐crystal forms it falls around δ =262 ppm.…”
Section: Resultsmentioning
confidence: 54%
“…It is likely that the chemical shifts of some of the protons are affected by intermolecular ring-current effects due to the edge-to-face herringbone structure of NPX-PA, which is similar to that of pure NPX (Carignani et al, 2013). Whilst the broad linewidths of 1 H SS-NMR can hinder the ability of SS-NMR to distinguish between protons in hydrogen bonds of the same type, there are many cocrystals/salts for which it is possible (Vogt et al, 2009;Gobetto et al, 2005;Sardo et al, 2015;Harris et al, 2010), including this case of NPX-PA. Not all 1 H peaks could be assigned, but the peaks of the two protons involved in the synthon E dimers, i.e. H31 and H361, can be distinguished.…”
Section: Figurementioning
confidence: 99%
“…Solid-state NMR (SS-NMR) is sensitive to the local structure, and NMR crystallography studies have been employed extensively to characterize hydrogen bonding in a variety of cocrystals (Harris et al, 2009;Stevens et al, 2014;Vogt et al, 2009;Gobetto et al, 2005;Chierotti & Gobetto, 2013;Brown, 2012), including cocrystals of NPX. For example, 2NPX-NA was investigated by two-dimensional (2D) 1 H-13 C heteronuclear correlation (HETCOR) experiments that confirmed the hydrogen-bonding network was a relatively rare example of a single carboxyl group giving rise to two different intermolecular synthons in the same cocrystal, probably due to the 2:1 stoichiometry (Ando et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Over the last decade, solid-state NMR (ssNMR) methods combined with computational chemical shift analysis 5,28,29 have been added to the inventory of techniques for the characterisation of hydrogen bonding and Brønsted interactions in the organic solid state. Studies have shown that H-bonding and proton transfer in two-component systems can be distinguished using 15 N ssNMR, 5,21,[29][30][31][32] as for example shown for co-crystals and salts of a cancer-treatment API 5 and for theophylline (1,3-dimethyl-7H-purine-2,6-dione) systems. 21,28,30 Density functional theory (DFT) can be applied to correlate 15 N ssNMR parameters with crystal structures.…”
Section: Introductionmentioning
confidence: 99%